2023
DOI: 10.3389/fmed.2023.982016
|View full text |Cite
|
Sign up to set email alerts
|

Shenkang injection combined with alprostadil for chronic renal failure: A systematic review and meta-analysis

Abstract: ObjectiveTo systematically evaluate the clinical efficacy and safety of Shenkang injection (SKI) combined with alprostadil in the treatment of chronic renal failure (CRF).MethodRandomized controlled trials (RCTs) of Shenkang injection combined with alprostadil in CRF treatment were investigated by retrieving a total of 7 databases including CNKI, Wanfang database, VIP, CBM, PubMed, Embase and Cochrane Library, with the search time ranging from 2012 to now. Revman 5.2 software was used for data analysis, and Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
0
1
Order By: Relevance
“…We noted that although the results of the present meta-analysis indicated that SKIs are effective in the treatment of AKI and that the results were more robust, the results of the present meta-analysis showed smaller decreases in various renal markers and greater heterogeneity in serum markers than did previous meta-analyses of SKI for the treatment of chronic kidney disease [ 28 ]. SKI is a Chinese medicinal preparation for CKD treatment, and there is no mention of how SKI should be used for treating AKI according to the expert consensus.…”
Section: Discussioncontrasting
confidence: 74%
“…We noted that although the results of the present meta-analysis indicated that SKIs are effective in the treatment of AKI and that the results were more robust, the results of the present meta-analysis showed smaller decreases in various renal markers and greater heterogeneity in serum markers than did previous meta-analyses of SKI for the treatment of chronic kidney disease [ 28 ]. SKI is a Chinese medicinal preparation for CKD treatment, and there is no mention of how SKI should be used for treating AKI according to the expert consensus.…”
Section: Discussioncontrasting
confidence: 74%